The influence of effectuation and technology orientation on firm performance in the renewable energy sector of South Africa - Heydenrych, James Andrew (My University, 2013)
This research study analyses a conceptual model investigating the effect of firms’ choice of effectuation or causation processes in strategy formation and firm performance, the effect of firms’ technology orientation in firm performance, and the relationship between effectuation and technology orientation. The study employed a quantitative approach, surveying data from 73 firms in the renewable energy sector of South Africa, using measurement instruments extracted from prior research. By means of multiple regression analysis, the study found that of the effectuation processes, the use of pre-commitments is significantly and positively associated with firm performance. Furthermore, it was found that a pioneering technology orientation is significantly and positively associated with firm performance. The study also found evidence to support the hypothesis that effectuation is closely linked with pioneering. The study contributes to the field of effectuation research by continuing to move the field towards an intermediate phase, by providing valuable insight into the practicalities of the quantitative analysis of effectuation and the problems that arise therein, in particular, issues surrounding measurement aspects. Moreover, by examining performance differentials, this study seeks to increase the relevance of effectuation theory and expand it from a theory of mere description of entrepreneurial behaviour to a theory that identifies performance-enhancing measures. For practitioners and policy makers, this research provides valuable insight into the drivers of entrepreneurial success and the fostering of entrepreneurial activity both in start-ups and existing corporations to spur innovation, productivity, and growth in the economy.
Thesis (M.M. (Entrepreneurship and New Venture Creation))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2013.
Keywords: Technology use; Organisational performance; Entrepreneurship; South Africa